Advances in the management of craniopharyngioma in children and adults - Jensterle Sever, Mojca (Radiology and oncology (Ljubljana), 2019)
Childhood and adult-onset craniopharyngioma is a rare embryogenic tumor of the sellar, suprasellar, and parasellar region. Survival rates are high; however, tumor location and treatment sequalae including endocrine deficits, visual impairment, metabolic complications, cognitive and psychosocial deficits can significantly impair patient%s quality of life. There is considerable controversy regarding the optimal management of craniopharyngiomas. Subtotal resection of the tumor followed by targeted irradiation to avoid further hypothalamic damage is currently indicated. Novel insights in the tumor%s molecular pathology present the possibility for targeted therapy possibly decreasing the rate and severity of treatment-associated morbidity. Conclusions. Craniopharyngioma should be seen as a chronic disease. To achieve optimal outcomes a multidisciplinary team of specialized neurosurgeons, neuro-radiologists, neuro-oncologists, pathologists and endocrinologists should be involved in the diagnosis, planning of the surgery, irradiation and long-term follow-up.
Keywords: hipopituitarizem; kraniofaringiom; presnovni sindrom